Estudo de sensores PZT aplicados à detecção de danos em tubulações - Pita Ruiz, Julián Leonel [UNESP] (2014)
In this work proposes the Structural Health Monitoring (SHM) in piping systems using the technique of Electromechanical Impedance (EMI), which is a form of non destructive Evaluation (NDE). The EMI technique is based on the Frequency Response Function (FRF) known for its simplicity and for the use of low cost piezoelectric transducers. Through the implementation of a SHM system on the pipes, if possible to monitor the structural integrity continuously, reducing the risk of accidents to the people and the environment. The proposed technique is based on the PZT transducers type, which are pasted on the curved surface of the main body of the pipe with a high stiffness adhesive. The sensors, properly positioned, are excited in a certain range frequency, generating a response that is measured by the electrical impedance. The process of monitoring the structural integrity of the pipes is done through periodic measurements of the impedance and the detection of damage is based on the responses changes. To detect the damage, the different measurements are analyzed using the traditional metric damage indexes in the area of ? SHM, the RMSD (Root Mean Square Deviation) and the CCDM (Correlation Coefficient Deviation Metric). The technique has demonstrated its ability to correctly identify the presence of damage on the main body of the pipes segments of the structures